Penerapan Toyota Business Practice (TBP) dalam Menurunkan Jumlah SPO Delay di PT TMMIN - Yosafat Cahya; Benedictus Rahardjo (Jurnal Titra, 2021)
PT. Toyota Motor Manufacturing Indonesia (PTTMMIN) is one of the major companies in Indonesia engaged in the automotive sector. PT TMMIN acts as a manufacturer and also as an exporter of cars and Toyota components. One component exported by PT TMMIN is a sample part which the component used as a trial for new project in the other Toyota affiliation. Export documents from sample parts called Sample Part Order (SPO). During handling, there are some SPO delayed which will have an impact on the company's Key Performance Indicator (KPI) and the image of PT TMMIN in the global affiliate as an exporter. An analysis to solve problems use Toyota Business Practice (TBP) tools and problem tree diagram. The improvements are summary of SPO, renewal of new phase 1 workflows, and weekly progress. The improvements have a positive effect, which reduce days of delay from 15 days to 0 days in the part confirmation, exporter reply delay decreasing from 71% on November 2018 into 0% delay on May 2019, also reducing delay shipment by 25% from November 2018 to 17% on May 2019. Expectations from the design of new information systems are to re-reduce the number of delays from SPO and facilitate the SPO handling process which benefits to PT TMMIN.